Cultural Translation, Long-form Journalism, and Readers’ Responses to the Muslim Veil - Conway, Kyle (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
This article examines, first, news translation as a form of cultural translation, and, second, readers’ responses to this mode of journalism. In particular, it examines the series Derrière le voile… des femmes, published in May 2010 by Radio-Canada.ca, through the lens of Hans-Georg Gadamer’s discussion of the I-Thou relationship, looking first at the stories in the series and then at readers’ comments. This series explained why some Muslim women chose to wear a niqab or veil, but the comments revealed that readers were largely unwilling to see the choice as one made freely. However, the comments also revealed that readers were willing to engage in conversation, pointing to one potential value of long-form interpretive journalism.